Analyses of burned area of forest by adaptive neuro-fuzzy approach - Jasmina Dedić; Srđan Jović; Jelena Đokić (Zaštita Materijala)
Burned area of forest may be developed based on different factors. In this investigation the burned area of forest was analyzed by computational intelligence approach. The main goal was to analyze the influence of eight inputs on the burned area of forest. The method of ANFIS (adaptive neuro fuzzy inference system) was applied to the data. Eight inputs are considered: FFMC, DMC, DC, ISI, temp, RH, wind, rain. The ANFIS process was implemented to detect the dominant factors which affect the forecasting of the burned area of forest.